Environmental federalism: a proposal of decentralization - María A. García-Vali\~nas (European Regional Science Association (ERSA), 2004)
In a context in which environmental protection have become in an important issue, the paper analyses which would be the optimal division of environmental policymaking functions among the different government levels. From the point of view of the fiscal federalism theory, we will design the most appropriate level of decentralization in each situation. In this sense, a proposal of decentralization has been shown, analyzing the consequences that a lax environmental policy could generate on future generations. Key words: Fiscal federalism, environmental policies, water management. Clasificación JEL: H77, Q25, Q28
Keywords: H77; Q25; Q28; 330; Fiscal federalism; environmental policies; water management Clasificación